Synesthesia dan Pengalaman Seni Fotografi - Marsiano Rocky Latuny; Handry Rochmad Dwi Happy (Jurnal Desain Komunikasi Visual Asia, 2023)
Photography is one branch of a large grouping in the arts, apart from design and painting. As a field of art, photography certainly has its own aesthetic concept, even the aesthetic concept is closely related to "feeling", an abstract concept regarding the process of absorbing something in human beings that cannot even be fully described. Understanding the concept of aesthetics is a dialectical process related to other issues such as philosophy, social, politics, culture, and economics so that the values ​​of goodness and truth often appear in a variety of aesthetic discussions. The development of an approach to the concept of the creation process that involves the audience and seeks to provide various stimuli for the five senses requires the ability to process other senses, namely connecting the five senses. The concept related to this is known as synaesthesia (synesthesia), a concept where the five senses work together at the same time when responding to a stimulus so that it will cause a sensation that exceeds the expression of one of the five senses. Understanding aesthetics with these various approaches is an active appreciation process that aims to uncover new discourse possibilities in the development of photography.